Peran Manajer Dalam Meningkatkan Kinerja Keuangan Bank OCBC Tbk - Yulfiswandi; Candy; Alzi; Miftachul Choiri; Brahmantya Chriswardhana; Jimmy Tjong (Fakultas Ekonomi dan Bisnis Universitas Satya Negara Indonesia, 2024)
The aim of the research was to observe and analyze the role of managers in banking financial reports. The research method uses a quantitative descriptive research model with PT. Bank Oversea-Chinese Banking Corporation NISP or PT. Bank OCBC NISP Tbk. as a research object. The sample is the financial report of PT. Bank OCBC NISP Tbk. from 2018 to 2022. The research results concluded that PT. Bank OCBC NISP Tbk. included in the category of